GAMBARAN SUBJECTIVE WELL-BEING DI PEKERJA HARIAN CV. CA - Yohanes Darmawan Setioko; Florentina Yuni Apsari (EXPERIENTIA : Jurnal Psikologi Indonesia, 2021)
Subjective well-being is defined as individual’s cognitive and affective evaluation towards individual’s own life, which can be observed through positive self-esteem, perceived control, extroversion, optimism, positive social relationship and feelings of purposeful and meaningful life. Subjective well-being is also influenced by individual’s work experience. Basing on the above-mentioned definition, this study is conducted to obtain a snapshot of the subjective well-being of daily workers that is considered one of the unstandardized employment. This study was conducted using qualitative approach of phenomenology. Data analysis was done using inductive thematic analysis. Informants of the study are daily workers who have long work experience in CV. CA. Result shows that daily workers of CV. CA fulfilled six aspects of subjective well-being including positive self-esteem, optimism, positive social relationship, perceived control, extraversion and feelings of purposeful and meaningful life. Keywords: subjective well-being, daily workers